INNOVATION AND CONTRIBUTION OF PRACTICAL FIQH IN THE HALAL INDUSTRY - Imroatul Azizah, Farida Isroani (STAI Syaichona Moh. Cholil Bangkalan, 2024)
The size of the Muslim market necessitates the growth and development of the halal industry, unfortunatelyThe Muslim community 'stutters' in dealing with this situation; not quickly seize opportunities as producers,but instead enjoy status only as consumers. Even in the era of free trade and market digitalization, variousinnovations are needed so that Muslims can capitalize on this potential. This research aims to examine theinnovations and contributions of fiqh in developing and reviewing shariah-compliant standards, procedures,and practices in the halal industry. This innovation is to ensure product halalness and meet the expectationsand needs of Muslim consumers. This qualitative research with phenomenology concludes that theinnovation and contribution of fiqh in the halal industry covers various aspects, such as the development ofprocessing technology; use of high-quality halal ingredients; creating new methods in production processesthat are more efficient and environmentally friendly; development of a more effective, more accessible andtransparent halal certification system; and increasing public education and awareness about halal products.After the production process and halal certification, it is still necessary to carry out an audit of the productionprocess and materials used, conduct research and analysis of relevant Sharia laws, and conduct consultationswith scholars and experts in their fields.